Left ventricular remodelling in bicuspid aortic valve disease - Butcher, Steele C (2022)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author(s) 2021. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)